High levels of opioid analgesic co‐prescription among methadone maintenance treatment clients in British Columbia, Canada: Results from a population‐level retrospective cohort study. (11th April 2014) - Nosyk, Bohdan; Fischer, Benedikt; Sun, Huiying; Marsh, David C.; Kerr, Thomas; Rehm, Juergen T.; Anis, Aslam H.
Abstract : Background and Objectives: The non‐medical use of prescription opioids (PO) has increased dramatically in North America. Special consideration for PO prescription is required for individuals in methadone maintenance treatment (MMT). Our objective is to describe the prevalence and correlates of PO use among British Columbia (BC) MMT clients from 1996 to 2007. Methods: This study was based on a linked, population‐level medication dispensation database. All individuals receiving 30 days of continuous MMT for opioid dependence were included in the study. Key measurements included the proportion of clients receiving >7 days of a PO other than methadone during MMT from 1996 to 2007. Factors independently associated with PO co‐prescription during MMT were assessed using generalized linear mixed effects regression. Results: 16, 248 individuals with 27, 919 MMT episodes at least 30 days in duration were identified for the study period. Among them, 5, 552 individuals (34.2%) received a total of 290, 543 PO co‐prescriptions during MMT. The majority (74.3%) of all PO dispensations >7 days originated from non‐MMT physicians. The number of PO prescriptions per person‐year nearly doubled between 1996 and 2006, driven by increases in morphine, hydromorphone and oxycodone dispensations. PO co‐prescription was positively associated with female gender, older age, higher levels of medical co‐morbidity as well as higher MMT dosage, adherence, and retention. Conclusion and Scientific Significance: A large proportion of MMT clients in BC received co‐occurring PO prescriptions, often from physicians and pharmacies not delivering MMT. Experimental evidence for the treatment of pain in MMT clients is required to guide clinical practice. (Am J Addict 2014;23:257–264)